Does extra staff change clinical practice? A prospective study of the impact of extra resources in mental health teams. - Kent, A; Fiander, M; Burns, T (2003)
OBJECTIVE: To compare patterns of clinical activity amongst existing staff in two inner-city community mental health teams before and after their enhancement with extra resources using a new activity schedule containing 11 comprehensive and mutually exclusive practice categories. METHOD: Patterns of clinical activity amongst existing members of two inner-London community mental health teams were compared before and after the addition of extra resources. RESULTS: The amount of time spent in face-to-face contact with patients and carers showed no meaningful change following team enhancement. Patterns of clinical activity amongst team members remained relatively static. CONCLUSION: Adding resources to community mental teams without considering how to target the time released amongst existing staff may reduce their capacity to work more innovatively.